Hole-bottom freezing technique based on phase change heat transfer for gas-hydrates sampling: Efficiency optimization of refrigeration change of phase. (5th February 2018) - Sun, Youhong; Wang, Yuan; Guo, Wei; Jia, Rui; Chen, Guanghua; Zhang, Pengyu
Highlights: Presenting the hole-bottom freezing method for gas-hydrate sampling. The vaporization efficiency of dry ice was improved. The effect of the frozen hydrate core was improved. The feasibility of hole-bottom freezing method was confirmed. Abstract: Coring is the key to the exploration and exploitation of natural gas hydrate. Less than 60% of gas-hydrate cores can be retrieved by the existing pressure preservation technique because of mechanical valve sealing failures. To solve this problem, a freezing sampling method was proposed. The cold-alcohol was formed by dry ice gasification refrigeration to reduce the temperature of the hydrate core in the drilling-hole and to prevent the decomposition of the gas-hydrates. However, gasification efficiency of dry ice in the narrow sampler's internal space is notably low, and the cryogenic alcohol cannot meet the requirements of the frozen hydrate core. In this paper, three different structures of the mixing chamber are proposed to improve the gasification efficiency of dry ice. The comparison mixing tests were performed with the cold-source external freezing sampler. The results demonstrate that cryogenic alcohol temperatures of 259.6 K, 248.3 K and 242.7 K are obtained using three kinds of mixing chambers, and the perforated pipe mechanism with the highest mixing efficiency was selected. The core and cold-alcohol heat transfer test demonstrates that the core was frozen to 254.7 K in 13 min. At this temperature, it is possible to ensure that the hydrate does not decompose.